Complex Problem Solving Beyond the Psychometric Approach - Magda Osman (Frontiers Research Topics, 2018)
Complex problem solving (CPS) and related topics such as dynamic decision-making (DDM) and complex dynamic control (CDC) represent multifaceted psychological phenomena. In abroad sense, CPS encompasses learning, decision-making, and acting in complex and dynamic situations. Moreover, solutions to problems that people face in such situations are often generated in teams or groups. This adds another layer of complexity to the situation itself because of the emerging issues that arise from the social dynamics of group interactions. This framing of CPS means that it is not a single construct that can be measured by using a particular type of CPS task (e.g. minimal complex system tests), which is a view taken by the psychometric community. The proposed approach taken here is that because CPS is multifaceted, multiple approaches need to be taken to fully capture and understand what it is and how the different cognitive processes associated with it complement each other.Thus, this Research Topic is aimed at showcasing the latest work in the fields of CPS, as well as DDM and CDC that takes a holist approach to investigating and theorizing about these abilities. The collection of articles encompasses conceptual approaches as well as experimental and correlational studies involving established or new tools to examine CPS, DDM and CDC. This work contributes to answering questions about what strategies and what general knowledge can be transferred from one type of complex and dynamic situation to another, what learning conditions result in transferable knowledge and skills, and how these features can be trained.